Leveraging user-generated content: A visual case analysis of Contiki’s brand co-creation campaign - Ouschan, Robyn; Turkington, J.; Napoli, Julie (Edward Elgar Publishing Limited, 2019)
A new area of customer engagement research which centers on the co-creation of brand content and brand meaning has emerged. Several researchers have highlighted the need for a more bottom up rather than top down approach to brand management is amplified because customer communication on social media has weakened the firm’s grip on their brands. This chapter illustrates the importance of leveraging user-generated content (UGC) as customers prefer and trust UGC, and user generated branding (UGB) presents an efficient and effective way to engage and enhance relationships with customers. To gain insight on how user-generated content co-creates brand meaning, this chapter presents a visual case analysis of the successful Contiki’s hashtag campaign ‘#noregrets’. Contiki is a global travel tour company offering group coach trips for ‘youth travelers’ (18_35 year-olds). The ‘#noregrets’ campaign encouraged Contiki travelers to share their travel photographs, which, if selected, were then reposted to Contiki’s official Instagram account. In this study, these images are analyzed using Schroeder’s critical visual analysis framework and in so doing, we integrate knowledge from the brand meaning and customer engagement literature to develop a deeper understanding of customer co-creation. We show how visual images are used to co-create brand meaning rather than more commonly researched online brand community narratives.